PERBAIKAN MANAJEMEN USAHA DAN PEMASARAN KEPADA PARA PELAKU UMKM KERAJINAN PEMBUATAN PIRING BERBAHAN DASAR LIDI DAUN KELAPA MUDA DI DESA WANASALAM KABUPATEN LEBAK BANTEN - Suhandi Suhandi; Normansyah Samiadji; Siti Nuraeni; Arif Mahmudin; Desi Sri Nurmala; Mela Nabila (LPPM Universitas Bina Bangsa, 2022)
The place for community service is the craftsmen of plate crafts made from young coconut tree sticks in Wansalam Village, Wanasalam District, Lebak Regency, Banten. The problems that occur in this area are as follows: craftsmen of plates made from young coconut tree sticks have not been able to apply management, cannot create quality products that are attractive and contemporary and have not been able to market their products. The training methods are: providing entrepreneurship material, business management, product innovation and product marketing. businesses, do not understand entrepreneurship, have not been able to create quality and attractive products, have not been able to market their products. So far, the business they run is a derivative business from their parents, the production process is still simple and marketing is in accordance with orders or requests from consumers